Effects of Training, Work Discipline, and Motivation Against Employee Performance at Islamic Bank - Muhammad Tho'in (Al-Tijary, 2018)
This study aims to determine whether training, work discipline, and motivation affect employee performance at Bank BNI Syariah Surakarta simultaneously and partially. This research uses case study research type which is located in Bank BNI Syariah Surakarta. The samples taken are 100 respondents. The sampling technique in this study used quota random sampling. The data analysis used are 1) Instrument Test, 2) Hypothesis test. The Result of this research shows that: Y = (11,877) + 0,784X1 + 0,444X2 + 0,428 X3 + e. There is an effect of training on employee performance of Bank BNI Syariah Surakarta with p-value <0,05. There is influence of work discipline on employee performance of Bank BNI Syariah Surakarta with p-value <0,05. There is influence of motivation to employee performance of Bank BNI Syariah Surakarta with p-value <0,05. There is an effect of training, work discipline, and motivation simultaneously on employee performance at Bank BNI Syariah Surakarta with p-value <0,05.